Population genetics of spinoсerebellar ataxias caused by polyglutamine expansions - A. N. Shuvaev; O. S. Belozor; M. V. Smolnikova; D. A. Yakovleva; Andr. N. Shuvaev; O. M. Kazantseva; E. A. Pozhilenkova; O. I. Mozhei; S. Kasparov (Вавиловский журнал генетики и селекции)
Hereditary disorders of the neuronal system are some of the most important problems of medicine in the XXI century. The most interesting representatives of this group are highly prevalent polyglutamine spinocerebellar ataxias (SCAs). It has a basement for quick progression of expansion among different groups all over the World. These diseases are SCA1, 2, 3, 6, 7 and 17, which phenotypically belong to one group due to similarities in clinics and genetics. The substrate of these genetic conditions is CAG trinucleotide repeat of Ataxin genes which may expand in the course of reproduction. For this reason a characteristic feature of these diseases is not only an increase in patient numbers, but also a qualitative change in the progression of their neurological symptoms. All these aspects are reflected in the structure of the incidence of polyglutamine SCAs, both at the global level and at the level of individual population groups. However, most scientific reports that describe the population genetics of polyglutamine SCAs are limited to quantitative indicators of a specific condition in a certain area, while the history of the occurrence and principles of the distribution of polyglutamine SCAs are poorly understood. This prevents long-term predictions of the dynamics of the disease and development of strategies for controlling the spread of mutations in the populations. In this paper we make a detailed analysis of the polyglutamine SCAs population genetics, both in the whole world and specifically in theRussian Federation. We note that for a better analysis it would be necessary to cover a wider range of populations in Africa, Asia andSouth America, which will be possible with the development of new methods for molecular genetics. Development of new methods of detection of polyglutamine SCAs will allow the scientists to better understand how they lead to the brain disease, the means of their spread in the population and to develop better methods for therapy and prevention of these diseases.